Unsteady numerical calculation of flow boiling heat transfer in microchannels with Kagome structures - Hongyu Wan; Jianxin Hu; Linsong Gao; Xun Miao; Yiyi Xu (Case Studies in Thermal Engineering)
A three-dimensional microchannel flow boiling model was developed based on the VOF model and the Lee model, and the flow and heat transfer in microchannels with Kagome structures were numerically simulated. The characteristics of bubble flow patterns, gas phase distribution, and heat transfer were analyzed under the heat fluxes of 5–8 MW/m2 and flow velocities of 0.2–0.5 m/s. The results show that at a flow velocity of 0.5 m/s, the disturbances caused by fluid impact on the Kagome structure result in bubble break-up, effectively suppressing the formation of large bubbles. However, at a flow velocity of 0.2 m/s, bubbles tend to be adhered on the surface of the Kagome structure, causing local blockage and deteriorating heat transfer. Compared to the flow velocity of 0.5 m/s, the average heat transfer coefficient in the microchannel decreases by up to 75.4 % and the pressure loss decreases by 45.38 % at the flow velocity of 0.2 m/s.